Balancing environmental impact: A sustainability index analysis of sorghum production for food and feed - A. Prabowo; R.N. Hayati; S. Minarsih; B. Haryanto; D.D. Ludfiani; A. Supriyo; S. Subiharta; E. Nurwahyuni; Y. Hindarwati; M.N. Setiapermas; S. Sudarto; S. Samijan; et al. (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: Sorghum is a grain-producing commodity with the seeds being a food source, while the leaves, stems, and bran serve as animal feed. The productivity depends on the specific variety, environment, infrastructure, and technology used. Sorghum cultivation in Indonesia is carried out primarily using agroforestry or monoculture. Despite not being as popular compared to rice and corn due to the prevalence of these staples in Indonesian diets, sorghum has the potential to replace corn because its cultivation is easier and the results are more profitable. Therefore, this study aimed to determine sustainability index and potential of sorghum for food and feed by identifying dimensions and attributes that influence sustainability.METHODS: This study was conducted at Raji, Demak, Central Java, Indonesia in 2023. Data were collected through focus group discussions and structural questionnaires consisting of 28 attributes associated with environmental, social, economic, and technological dimensions. Multidimensional scaling method and Rapfish software were used for data analysis. Monte Carlo analysis was used to ascertain sustainability level and attributes leverage, as well as check errors and variations in assessment.FINDINGS: The results showed that sustainability index of sorghum for food and feed was 79.67, categorized as very sustainable. Analysis across four dimensions showed that the social dimension had the highest (83.80) sustainability index, followed by the technological (82.28), economical (77.46), and environmental (75.15) dimensions. A total of 12 attributes were found to greatly affect sustainability. These included land availability, the efficiency of water used, the prevention of natural resource exploitation, motivation level, minimal interference with primary agricultural activities, community acceptance, productivity, sales profit level, ease of sale and cultivation, tools availability, and technological sensitivity.CONCLUSION: Sustainability index of sorghum for food and feed was categorized as very sustainable with a value of 79.67. This index consisted of the environmental (75.15), social (83.80), economical (77.46), and technological dimensions (82.28). The average productivity at the study site was 6-7 tons per hectare, with a production potency of 300-350 tons per year. Additionally, the potency of sorghum stover production was 471.8 ton per year of dry matter and could be used as feed for 163 animal units per year